Bibliometric analysis of physical education learning in inclusive schools: trends, contributions, and research impact - Deswita Supriyatni; Soni Nopembri; Hari Yuliarto; Sandey Tantra Paramitha; Muhammad Gilang Ramadhan; Eko Purnomo (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Physical education in inclusive schools is increasingly gaining attention as a research area that is often studied by researchers in various countries. In the development of the inclusive education system, it is important to understand the main trends in this study.